Influence of processing temperature on properties of Sr(Fe0.5Nb0.5)O3high dielectric ceramics - Chatchai Kruea-In (2018)
Influence of processing parameters, calcination and sintering temperatures, on the properties of Sr(Fe0.5Nb0.5)O3samples were investigated The Sr(FeL0.5Nb0.5)O3ceramics were fabricated by a solid-state reaction method. X-ray diffraction analysis revealed that pure perovskite phase of SFN powders was observed for the calcination temperatures ≥1000°C. However, all SFN ceramics showed the pure perovskite phase. Average grain size increased with increasing sintering temperature, where the hardness value was related with grain size. The dielectric properties examination indicated that increase of the sintering temperature is effective in improving dielectric constant of the SFN ceramics. © 2013 Copyright Taylor and Francis Group, LLC.